Early Childhood Policies and Systems in Eight Countries Findings from IEA's Early Childhood Education Study - Bertram, Tony; Pascal, Chris (Springer International Publishing : Imprint: Springer, 2016)
This report provides an overview of policy strategies on early childhood education settings (from birth to primary schooling) in eight countries. Data were collected using a policy questionnaire addressed to and completed by the National Research Coordinator(s) (NRC) of Chile, the Czech Republic, Denmark, Estonia, Italy, Poland, the Russian Federation and the United States. The countries that participated provide interesting illustrations of early childhood education policy in action in a range of diverse contexts. Analysis of the systemic and structural results of ECE policy at national and, where necessary, subnational levels, enables transnational comparisons in policy and systems. Key policy changes, both underway and planned, are documented. These data reveal key findings in each of the five policy areas as covered in the questionnaire and this report: public policy; delivery models and providers; participation and enrollment; quality assurance systems; and expectations for child outcomes. In particular, the study aims to provide meaningful information for countries, states and jurisdictions across the world in relation to early childhood education, mapping the systems, structures and user pathways in place, along with the perceptions of stakeholders about the system, its functioning and impact. This comprehensive assessment of the wider policy contexts and settings for early childhood education includes teacher/practitioner qualifications, pedagogy approaches, and opportunities for professional development. Such information will enable countries to review their early childhood education systems in an international context.